2011
DOI: 10.1167/iovs.10-6805
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Magnetic Resonance Imaging of the Phakic Crystalline Lens during Accommodation

Abstract: During accommodation, mean crystalline lens thickness increased (F = 33.39, P < 0.001), whereas lens equatorial diameter (F = 24.00, P < 0.001) and surface radii both decreased (anterior surface, F = 21.78, P < 0.001; posterior surface, F = 13.81, P < 0.001). Over the same stimulus range, mean crystalline lens surface area decreased (F = 7.04, P < 0.005) with a corresponding increase in lens volume (F = 6.06, P = 0.005). These biometric changes represent a 1.82% decrease and 2.30% increase in crystalline lens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 52 publications
5
63
3
Order By: Relevance
“…The change in lens thickness with accommodation has been well documented by multiple independent studies, and the parameters reported in the current study fall well within previously reported ranges. 27,41,[59][60][61][62] Nonhuman primate studies have demonstrated an accommodative decrease in LED of approximately 0.055 mm/D. 15,63 Only in the last decade have human studies reported in vivo changes in LED in enough people to accurately quantify this parameter in humans.…”
Section: Ocular Dimensions With Agementioning
confidence: 99%
“…The change in lens thickness with accommodation has been well documented by multiple independent studies, and the parameters reported in the current study fall well within previously reported ranges. 27,41,[59][60][61][62] Nonhuman primate studies have demonstrated an accommodative decrease in LED of approximately 0.055 mm/D. 15,63 Only in the last decade have human studies reported in vivo changes in LED in enough people to accurately quantify this parameter in humans.…”
Section: Ocular Dimensions With Agementioning
confidence: 99%
“…On the other hand, the positive use of MRI in real-time measurements of water transport in the lens has been reported by previous studies (27)(28)(29). Sheppard et al showed the successful use of MRI for the measurement of mean crystalline lens thickness during accommodation (13). Van Rijn et al reported that IOLs are compatible with MRI (12).…”
Section: Discussionmentioning
confidence: 89%
“…The results of a study performed by Van Rijn et al demonstrated that IOLs are compatible with MRI at a magnetic field strength of 7 Tesla (12). Sheppard et al after evaluation of three-dimensional MRI of the phakic crystalline lens during accommodation, reported that mean crystalline lens thickness increased during accommodation (13).…”
Section: Introductionmentioning
confidence: 99%
“…The lens reduces in diameter, and becomes thicker axially accompanied by a similar reduction in anterior chamber depth and a small reduction in vitreous depth [2,3]. Strenk et al reported increase in cross-sectional area of the anterior portion of the lens with accommodation [4], but others had reported small decreases in cross-sectional area with accommodation [5,6]. Small increases [5] or no changes [6,7] in volume with accommodation have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Strenk et al reported increase in cross-sectional area of the anterior portion of the lens with accommodation [4], but others had reported small decreases in cross-sectional area with accommodation [5,6]. Small increases [5] or no changes [6,7] in volume with accommodation have been reported. Accompanying the changes in the external geometry of the lens is a change in the gradient refractive index distribution (GRIN) inside the lens [8].…”
Section: Introductionmentioning
confidence: 99%